ANALISIS PERSEPSI AKADEMISI DAN PRAKTISI TERHADAP FRAUD SERTA PERAN WHISTLEBLOWING SEBAGAI UPAYA PENCEGAHAN DAN PENDETEKSIAN FRAUD - Wiwit Hariyanto (GREENOMIKA, 2022)
The purpose of this study was to examine more deeply how the perception of academics (professors and students) and practitioners of the accounting practices of fraud as well as the role of whistleblowing for prevention and detection of fraud. This type of research is using qualitative methods using natural setting that aims to describe the circumstances (phenomenon) that happens. The data analysistechnique used is data collection, data reduction, a data display and conclusion drawing/ verifying. Based on the results of research and discussion concluded that the perception of academics (professors and students) accounting and practitioners are almost entirely have to have a good understanding of fraud and whisleblowing for prevention and detection of fraud. This indicates that of University of Muhammadiyah Sidoarjo has the potential to become a whisleblower and for PT. PG Candi Baru shows that this company has the potential to further improve good governance in the public sector because with a good understanding of these conditions, the potential for the occurrence of acts of fraud will getting smaller